Innovation crisis in design studios: whom to blame? / Bhzad Sidawi - Sidawi, Bhzad (Faculty of Architecture, Planning & Surveying and UiTM Press, 2013)
Design is a social phenomenon and researchers suggest that communications and negotiations between designers are essential to initiate creativity. Within the design studio environment, the social interaction and design negotiations between students and tutors and with their mates is influenced by a number of factors that hinder students from fully utilizing it in the design scheme. Design studios' students from the third to fifth year at the College of Architecture, UoD were surveyed the influences on the production of innovative design projects. The research found a number of potential interrelated factors that would play a negative role in hindering student's creativity. However, to develop students' design/innovative abilities, the researcher recommends that certain measures should be considered. These would include the use of innovative design precedents, development of students and tutors' communications skills, and transformation of the design studio into interactive and friendly learning environment that motivate students to produce innovative design projects.